Regulating Utilization Efficiency of the Photogenerated Charge Carriers by Constructing Donor–π–Acceptor Polymers for Upgrading Photocatalytic CO2 Reduction. Issue 13 (26th May 2021) - Chen, Jinqing; Zhong, Hong; Lv, Haowei; Liu, Ruixia; Wang, Ruihu
Abstract: Photocatalytic CO2 reduction offers a promising approach for managing global carbon balance. The smooth delivery of the photoexcited electrons to the active sites without the extra photosensitizers is still challenging. Herein, a series of donor–π–acceptor conjugated organic polymers (COPs) were produced using anthracene, cobalt‐coordinated bipyridyl, and benzene as donor, acceptor, and π linker units, respectively. The introduction of phenyl linker significantly improved the activities of photocatalytic CO2 reduction upon visible light illumination. Structure–performance relationship examinations uncovered that donor–π–acceptor structure promotes mobility of charge carriers and utilization efficiency on the catalytically active sites, resulting in high photocatalytic activity and durability for CO2 photoreduction. The in‐depth insights into the electron transport processes open new perspectives for further optimization and rational design of photoactive polymers with high efficiency for solar‐energy conversion. Abstract : Life of π : The photocatalytic activity for CO2 reduction is significantly enhanced through the incorporation of π linker into D‐A structure to build D–π–A photocatalysts. The extended conjugation degree from π linker facilitates the separation and utilization of photogenerated electrons. This work provides an ideal platform for molecular‐level modulation into charge transfer in photocatalytic CO2 reduction.